Novel biomarkers in cancer: The whole is greater than the sum of its parts. (August 2017) - Samatov, Timur R.; Galatenko, Vladimir V.; Block, Andreas; Shkurnikov, Maxim Yu.; Tonevitsky, Alexander G.; Schumacher, Udo
Abstract: The major issues hampering progress in the treatment of cancer patients are distant metastases and drug resistance to chemotherapy. Metastasis formation is a very complex process, and looking at gene signatures alone is not enough to get deep insight into it. This paper reviews traditional and novel approaches to identify gene signature biomarkers and intratumoural fluid pressure both as a novel way of creating predictive markers and as an obstacle to cancer therapy. Finally recently developed in vitro systems to predict the response of individual patient derived cancer explants to chemotherapy are discussed.